The access to justice of children and adolescents in Spain: Towards an integral accomplishment of the 100 Brasilia Rules on Access to Justice for Persons in Conditions of Vulnerability - Ortega Ortigoza, Daniel (2021)
This essay analyzes a long-standing problem in Spain: access to justice for children and adolescents who have suffered violence, as part of the conglomerate of people in vulnerable conditions. It mentions the successive legislative bodies enacted in Spain, which had the International Convention on the Rights of the Child and the 100 Rules of Brasilia as a guideline and basis. In addition, it explains the new regulations that must be implemented to prevent the re-victimization of the child during the long judicial process.